DIGITAL MARKETING KEKINIAN BAGI UMKM KRIWAKZ KERIPIK IKAN WADER RAWA SALATIGA - Widaryanti Widaryanti; Luhgiatno Luhgiatno; Maduretno Widowati (Universitas YPPI Rembang, 2021)
Swamp wader chips are one of the snacks or snacks made from wader fish. The nutritional content of swamp wader fish is very high, this can be used as an alternative to providing nutritious food at affordable prices for all people. Some of the wader swamp iwak chips businesses are still on the scale of home industries or micro, small and medium enterprises (MSMEs). One of the SMEs that sells wader swamp fish chips is the SMEs